2012
DOI: 10.1088/1742-5468/2012/10/p10026
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement versus mutual information in quantum spin chains

Abstract: The quantum entanglement E of a bipartite quantum Ising chain is compared with the mutual information I between the two parts after a local measurement of the classical spin configuration. As the model is conformally invariant, the entanglement measured in its ground state at the critical point is known to obey a certain scaling form. Surprisingly, the mutual information of classical spin configurations is found to obey the same scaling form, although with a different prefactor. Moreover, we find that mutual i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…Note that the mutual information is symmetric with respect to A and B, and that the leading contributions proportional to L cancel in the definition (3). It has been first studied for the Ising universality class 29,30 , and the scaling argued to be universal. More precisely, it was found that the Shannon mutual information (SMI) is well described by the following formula:…”
Section: I(a B) = S(a) + S(b) − S(a ∪ B) (3)mentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the mutual information is symmetric with respect to A and B, and that the leading contributions proportional to L cancel in the definition (3). It has been first studied for the Ising universality class 29,30 , and the scaling argued to be universal. More precisely, it was found that the Shannon mutual information (SMI) is well described by the following formula:…”
Section: I(a B) = S(a) + S(b) − S(a ∪ B) (3)mentioning
confidence: 99%
“…[1] compared to Refs. [29][30][31], for different models and limits belonging to the Ising universality class. On the conceptual level also, the result appears much simpler than previous findings in the Shannon entropy of the full chain 15,18,20 .…”
Section: I(a B) = S(a) + S(b) − S(a ∪ B) (3)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the first case we use the ground state of the quantum system as the source of the probabilities for appearing different configurations and in the second case it will be just the Gibbs distribution. The first definition which has recently found many interesting applications in the study of spin chains 38,[40][41][42] can be defined in the context of harmonic oscillators as follows: The Shannon's classical mutual information I(A : B) between two regions A and B is…”
Section: Mutual Informationmentioning
confidence: 99%
“…They found that although the mutual information of two halves of a cylinder has its maximum value at a temperature higher than the critical temperature, its derivative diverges at the critical temperature. Most recently Um et al [16] studied the mutual information of a subregion with respect to the rest in the periodic transverse Ising model and surprisingly found that it has the same dependence ln(sin(πℓ/L)) as (1) but with a distinct multiplicative constant. In this Letter we study the Shannon mutual information of local observables in different critical spin chains and argue about their possible connections to the central charge of the underlying CFT.…”
mentioning
confidence: 99%